Features of the iSCSI protocol. - Meth, K.Z (IEEE Communications magazine)
The iSCSI protocol specifies how to access SCSI storage devices over a TCP network. In this article we give a brief introduction to the iSCSI protocol and a brief comparison with alternative technologies. We then discuss the basic features of the iSCSI protocol: sessions, naming, discovery, security, data placement, and recovery.